Kontribusi Abdullah bin Nuh dalam Pengembangan Pendidikan Islam di Cianjur, Sukabumi dan Bogor, Jawa Barat. - Sutopo Sutopo; Misno Misno (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
the spread of Islam in West Java region in the second period was done by the scholars who studied in the Middle East especially Saudi Arabia and Egypt. One of the spreaders of Islam in the West Java region especially in Cianjur, Sukabumi and Bogor is KH. Abdullah bin Noah. He has kemamampuan in the field of da'wah, journalist, educator, soldier, historian, Writer, and an Islamic Thinker. This article will examine how his contribution in the field of Islamic studies in the area of Cianjur, Sukabumi and Bogor. The Thought Of KH. Abdullah bin Noah about the concept of education contained in the 18 books he wrote include translation entitled ' Minhaj al ' Abidin ' of Priest Ghozali. The real leadership of the Islamic education form KH. Abdullah Ibn Nuh was marked by the establishment of the YIC (Foundation Islamic Centre) based in Bogor with a focus on education and Dawah of Islam.